1985
DOI: 10.1254/jjp.39.323
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemic Effects of Adriamycin in Rats

Abstract: Abstract-Adriamycin, an anticancer drug, caused dramatic increases in the serum lipid levels of rats fed a high-cholesterol diet. Male Lewis inbred rats were fed a basal or 1.5% cholesterol diet containing 0.5% cholic acid for 8 weeks.The rats were injected with adriamycin in doses of 1.5 mg/kg body weight, twice a week, and 6.0 mg/kg body weight, every other week. The serum lipid peroxide level gradually rose in adriamycin-treated rats, reaching a four-fold level at the end of the experiment.Cholesterol feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…Values expressed as mean ± SD. a week, and it has also indicated a decrease in ALT and AP activities compared with controls [26]. AST and AP values in our study are in accordance with their results, but the increase in ALT value differs from the results of their study.…”
Section: Discussionsupporting
confidence: 86%
“…Values expressed as mean ± SD. a week, and it has also indicated a decrease in ALT and AP activities compared with controls [26]. AST and AP values in our study are in accordance with their results, but the increase in ALT value differs from the results of their study.…”
Section: Discussionsupporting
confidence: 86%
“…The role of cholesterol in adjuvant arthritis has not been studied, but we observed that cholesterol feeding could lower the serum lipid peroxide level. Similar results have been obtained in a previous study (21). The relation of lipid peroxidation to adjuvant arthritis (26) and rheumatoid arthritis (27) has been reported.…”
Section: Discussionsupporting
confidence: 91%
“…However, the rat is quite resistant and cholesterol feeding alone does not produce atherosclerotic lesions. In previous studies (21,22) as well as in the present one, no significant accumulation of cholesterol in the aorta was observed in rats, despite the fact that sufficient hypercholesterolemia was achieved by cholesterol feeding alone. For the rat, vascular injury in combination with hypercholesterolemia is necessary for lipids to accumulate on the arterial wall (3,8,22,23).…”
Section: Discussionsupporting
confidence: 48%
“…The levels of cholesterol in the aorta were determined by a fluorometric enzymatic method. 12) Briefly, 200 ml of extract and 2.5 mg of Triton X-100 were mixed and evaporated under a vacuum. The residue was suspended with 200 ml of the enzyme mixture and the suspension was incubated for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%